Analisis Kualitatif Penurunan Prestasi Tim Indonesia Pada Cabang Olahraga Tenis di Sea Games 2022 - Bana, Panji; Fithroni, Hijrin; Hariyanto, Agus; Rusdiawan, Afif (Jurnal Porkes, 2022)
The purpose of this study was to qualitatively analyze the decline in the performance of the Indonesian tennis team at the 2022 Sea Games. This research is an evaluation study with a qualitative approach. A total of 5 people were used as subjects in this study consisting of 3 male athletes, 1 female athlete and 1 coach who had departed as the 2022 Sea Games team for tennis. Data collection uses interview techniques which are conducted online through the zoom meeting application. Data analysis used thematic analysis through the stages of data reduction, organization and interpretation assisted by atlas.ti 9 software. The results of the study showed that the coaching factor and infrastructure were good. The composition of Indonesian players is not optimal and the opponents are playing optimally at the 2022 Sea Games as well as the pandemic factor which has caused a decline in tennis performance at the 2022 Sea Games. The conclusion is that the reason for the decline in Indonesia's tennis achievements at the 2022 Sea Games is not due to the poor coaching process and infrastructure, but due to the different composition of the players and the impact of the covid-19 pandemic.